2020
DOI: 10.1186/s13028-020-00558-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic imaging of police working dogs with bilateral naturally occurring hip osteoarthritis

Abstract: Background Digital thermal imaging is a physiologic, non-invasive, contactless, and non-radiating diagnostic tool that can assess a wide range of musculoskeletal conditions, including hip osteoarthritis (HOA). Fifty police working dogs were evaluated to compare the dorsoventral (DV) and lateral (LT) thermographic images in dogs with naturally occurring bilateral HOA. A DV, and left and right lateral LT images were obtained for each animal in six different moments. They were positioned standing in a symmetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A previous study showed that German Shepherd dogs have lower values during thermographic evaluation than the other considered breeds. 48 The animals included in this study had short hair, and some had a double coat. The breeds included were similarly distributed between groups, which may help balance these differences.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that German Shepherd dogs have lower values during thermographic evaluation than the other considered breeds. 48 The animals included in this study had short hair, and some had a double coat. The breeds included were similarly distributed between groups, which may help balance these differences.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in dogs to help locate the site of OA by measuring body surface temperature ( 115 ) and was found to be capable of differentiating between normal and diseased joints ( 116 , 117 ). More recently, its use in OA identification within a working dog population has been explored ( 118 , 119 ). However, body surface temperature can be affected by hair coat characteristics ( 120 ) and by coat clipping ( 121 ), which can complicate the interpretation of the thermograms.…”
Section: Nuclear Medicine and Othersmentioning
confidence: 99%
“…The main disadvantage is that it does not show any ability to recognize the etiology of the disease, but only the thermal alteration [1]. Current applications in veterinary medicine include neoplasia diagnosis [3], assessment of orthopedic and neurological diseases [4][5][6][7][8][9][10][11][12] as well as the effects of exercise on thermal images [13][14][15]. Indeed, internal and surface temperatures are influenced by physical exercise [14].…”
Section: Introductionmentioning
confidence: 99%